1993
DOI: 10.1108/09590559310028040
|View full text |Cite
|
Sign up to set email alerts
|

Supermarket Shopping Lists: Their Effect on Consumer Expenditure

Abstract: The presence of a written shopping list on a major grocery buying trip to the supermarket is tangible evidence of out‐of‐store planning by the shopper. This pre‐planning may influence both time spent in store and grocery expenditure, two factors of importance to supermarket retailers. Set in a New Zealand city, examines the extent to which a written grocery shopping list affects these two factors by comparing the behaviour of two matched samples, one with lists and one without. The findings are conclusive: wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 5 publications
4
46
0
1
Order By: Relevance
“…The ability to maintain self-control and successfully take long-term decisions depends on the strength of these two opposing processes. If we consider the grocery context, there are two ways to control shopper impulsivity: define a mental budget to be followed during shopping expedition (Heat & Soll, 1996;Stilley, Inman, & Wakefield, 2010), and devote time to the preparation of the trip (Heckhausen & Gollwitzer, 1987;Iyer & Ahlawat, 1987;Thomas & Garland, 1993;Thomas & Garland, 2004). According to Stilley, Inman, & Wakefield (2010) shoppers have a mental budget composed of two parts: a section dedicated to planned purchase and a part not assigned to any product in particular, in order to anticipate the possibility of making impulsive purchases.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to maintain self-control and successfully take long-term decisions depends on the strength of these two opposing processes. If we consider the grocery context, there are two ways to control shopper impulsivity: define a mental budget to be followed during shopping expedition (Heat & Soll, 1996;Stilley, Inman, & Wakefield, 2010), and devote time to the preparation of the trip (Heckhausen & Gollwitzer, 1987;Iyer & Ahlawat, 1987;Thomas & Garland, 1993;Thomas & Garland, 2004). According to Stilley, Inman, & Wakefield (2010) shoppers have a mental budget composed of two parts: a section dedicated to planned purchase and a part not assigned to any product in particular, in order to anticipate the possibility of making impulsive purchases.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Grocery shopping preparation is a self-control strategy which is adopted by consumers in order to limit impulse purchases (Iyer & Ahlawat, 1987;Thomas & Garland, 1993;Thomas & Garland, 2004;Heckhausen & Gollwitzer, 1987). In the new market scenario, characterized by the presence of multiple tools -online and offline -which allow customers to collect information, it is interesting to investigate what kind and how many pre-trip activities consumers carry out in order to control their budget Q2 -Does the grocery shopping preparation influence the shopping behaviour in-store?…”
Section: Research Questionsmentioning
confidence: 99%
“…The earlier studies discussed above were all based on interviews with a sample of respondents. For instance Spiggle's (1987) study is based on 129 interviews while Thomas and Garland (1993) interviewed 232 shoppers out of which half used a shopping list. Our own study employs a purely unobtrusive approach implying that we analyse shopping lists without any knowledge about background characteristics of shoppers.…”
Section: Methodological Approach Of the Present Studymentioning
confidence: 99%
“…1 Rickard (1995) reports that 55% of shoppers make lists. According to the IPC Women's Weekly Group Survey (1970), cited in Thomas and Garland (1993), as many as three out of four housewives employ written lists. Thomas and Garland's own studies showed 61% (1993) and 67% (2004).…”
Section: The Shopping List As Vehicle For Goal Achievementmentioning
confidence: 99%
“…Generally, national food brands were perceived as superior to own labels in terms of quality, packaging, consistency and good image [11] (Omar, 1996) . Written shopping lists significantly reduce average expenditure and the presence of children accompanying the shopper significantly increases expenditure and time spent in store [18] (Thomas and Garland, 1993). The major drivers for choosing a grocery store in India seem to be nearness to place of residence and the comfort level that the respondents has in dealing with the store owner measured in terms of personal relationship with the shopkeeper [14] (Sinha and Banerjee, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%